Radiation production using femtosecond electron bunches - C. Thongbai (2018)
Femtosecond electron bunches can be generated from a system consisting of an RF gun with a thermionic cathode, an alpha magnet, and a linear accelerator and can be used to produce femtosecond (fs) electromagnetic radiation pulses. At the Fast Neutron Research Facility (FNRF), Thailand, we are especially interested in production in Far-infrared (FIR) and x-radiation. In the farinfrared, radiation is emitted coherently for wavelengths which are longer than the electron bunch length, yielding intense radiation. Although, the x-rays emitted are incoherent, its femtosecond time scale is crucial for development of a femtosecond x-ray source. © 2005 Trans Tech Publications, Switzerland.